METHODS OF THE DEVELOPMENT OF PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF YOUNG FOOTBALL PLAYERS - Kadirov, Abdurashid (Журнал иностранных языков и лингвистики, 2022)
It can be inferred that the game of football requires the development of physical qualities and psychophysiological well-being because complex technical techniques in football match can only be conduct with perfect central nervous system. That is why many well-known authors, who had been paying great attention to the problem of controlling movements by the central nervous system, pointed out that it is of paramount importance to determine the status of the nervous system in the formation of motor skills. This article covers various aspects of targeted functional training of young football players. The structural features of the functional readiness of young football players are described. Methodical approaches to the organization of differentiated functional training of young football players depending on the game specialization in different periods of the training macrocycle based on the use of additional ergogenic means are given. The main directions and substantiation of the technology of general psycho-functional training are presented, ways of increasing the reliability of target motor actions of young football players based on biofeedback are shown.